The Influence of Inflation on Economic Growth in Indonesia During the 2016-2020 Period - Nathania Christy Sembiring; Hottarida Sinaga; Respa Mellia Sirait (International Journal For Advanced Research, 2025)
This study aims to analyze the impact of inflation on Indonesia's economic growth during the 2016-2020 period. Inflation is a key macroeconomic indicator with complex effects on economic activity, both positive and negative. A quantitative method with a descriptive-analytical approach was employed, using secondary data from Statistics Indonesia and Bank Indonesia. A simple linear regression analysis revealed that inflation has a significant effect on economic growth, with a significance level of 0.039. The findings indicate that rising inflation, particularly during the Covid-19 pandemic, negatively impacted economic growth due to increased prices of essential goods, reduced purchasing power, and higher unemployment. However, inflation levels during the observed period remained within a normal range, offering opportunities to drive further economic growth. This study provides valuable insights for policymakers in managing inflation to support economic stability and sustainable growth.